Autonomous Optofluidic Chemical Analyzers for Marine Applications: Insights from the Submersible Autonomous Moored Instruments (SAMI) for pH and pCO2 - Lai, Chun-Ze; DeGrandpre, Michael D.; Darlington, Reuben C. (Frontiers in Marine Science, 2018)
The commercial availability of inexpensive fiber optics and small volume pumps in the early 1990’s provided the components necessary for the successful development of low power, low reagent consumption, autonomous optofluidic analyzers for marine applications. It was evident that to achieve calibration-free performance, reagent-based sensors would require frequent renewal of the reagent by pumping the reagent from an impermeable, inert reservoir to the sensing interface. Pumping also enabled measurement of a spectral blank further enhancing accuracy and stability. The first instrument that was developed based on this strategy, the Submersible Autonomous Moored Instrument for CO2 (SAMI-CO2), uses a pH indicator for measurement of the partial pressure of CO2 (pCO2). Because the pH indicator gives an optical response, the instrument requires an optofluidic design where the indicator is pumped into a gas permeable membrane and then to an optical cell for analysis. The pH indicator is periodically flushed from the optical cell by using a valve to switch from the pH indicator to a blank solution. Because of the small volume and low power light source, over 8,500 measurements can be obtained with a ~500 mL reagent bag and 8 alkaline D-cell battery pack. The primary drawback is that the design is more complex compared to the single-ended electrode or optode that is envisioned as the ideal sensor. The SAMI technology has subsequently been used for the successful development of autonomous pH and total alkalinity analyzers. In this manuscript, we will discuss the pros and cons of the SAMI pCO2 and pH optofluidic technology and highlight some past data sets and applications for studying the carbon cycle in aquatic ecosystems.